(NmUZYKALXNAQ LITERATURAs - (Ni(B. (NgIWENTALXs; (Nl(B. (NgINGOLXDs ((NmOSKWAs (NmUZYKAs, 1976)
(Nw POSOBII DAETSQ OB]AQ HARAKTERISTIKA TWOR^ESTWA I ANALIZ KRUPNYH INSTRUMENTALXNYH PROIZWEDENIJs
Keywords: (NISTORIQs